Britain's pacification of Palestine the British Army, the colonial state, and the Arab revolt, 1936-1939 - Hughes, Matthew 1965- (Cambridge University Press, 2020)
"In this complete military history of Britain's pacification of the Arab revolt in Palestine, Matthew Hughes shows how the British Army was so devastatingly effective against colonial rebellion. The Army had a long tradition of pacification to draw upon to support operations, underpinned by the creation of an emergency colonial state in Palestine. After conquering Palestine in 1917, the British established a civil Government that ruled by proclamation and, without any local legislature, the colonial authorities codified in law norms of collective punishment that the Army used in 1936. The Army used 'lawfare', emergency legislation enabled by the colonial state, to grind out the rebellion. Soldiers with support from the RAF launched kinetic operations to search and destroy rebel bands, alongside which the villagers on whom the rebels depended were subjected to curfews, fines, detention, punitive searches, demolitions and reprisals. Rebels were disorganised and unable to withstand the power of such pacification measures"...
Keywords: HISTORY / Military / General / bisacsh; Counterinsurgency -- Palestine -- History -- 20th century; Mandates -- Palestine -- History -- 20th century; Imperialism -- History -- 20th century; HISTORY / Military / General; Arabischer Aufstand -- 1936-1939; Palestine -- History -- 1917-1948; Palestine -- Politics and government -- 1917-1948; Great Britain -- Foreign relations -- Palestine; Palestine -- Foreign relations -- Great Britain; Großbritannien; Palästina